Polarization-independent high-sensitive metamaterial sensor for chemical sensing and EMI shielding application - Md Kutub Uddin; Shawon Hossen; Touhidul Alam; Mohammad Tariqul Islam; Saleh Albadran; Haitham Alsaif; Ahmed S. Alshammari; Ahmed Alzamil; Mohammad Lutful Hakim (Engineering Science and Technology, an International Journal)
Chemical sensing is essential for characterizing liquid chemical samples in the chemical industry. Consequently, Electromagnetic interference (EMI) shielding is crucial for promising the reliable functioning of diverse electronic devices. This study proposes a polarization-independent high-sensitive quadrant-shaped metamaterial (QM) sensor for chemical sensing and effective electromagnetic interference (EMI) shielding applications. The metamaterial (MTM) is specifically developed to demonstrate a polarization-insensitive electromagnetic (EM) response, which has a high sensitivity level for chemical sensing. This study explores the EMI shielding and sensor performance using a 0.33λ × 0.33λ × 0.052λ mm3 Rogers RT5880 substrate. This MTM-based sensor exhibits resonance at 10 GHz for both transverse electric (TE) and transverse magnetic (TM) modes. Besides, the transmission coefficient(S21) is investigated at different φ-angle and θ-angle, where φ-angle and θ-angle are applied up to 90˚ and 75˚ for TE and TM modes. Furthermore, To validate the designed MTM, a 40 × 50 mm2 array prototype is fabricated, and the performance of the MTM is investigated in the laboratory, where the real-time investigation results strongly agree with the simulation result. Besides, the unit cell structure can be utilized as a sensor for detecting different liquid chemical substances. The sensor model achieves a high sensitivity of 18.87 as well as a high-quality Factor (Q-Factor) of 475. The MTM sensor also has a significant Figure of Merit (FoM) of 4411.80, which is a significant achievement for sensing technology. Therefore, The proposed compact and polarization-insensitive MTM has possibilities in various sensing industries, including telecommunications and liquid chemical substance monitoring, and it shows promise for improvements in chemical industries and EMI shielding technologies.